Alms-Giving and Financial Management - Agustin, Grisvia; Sumanto, Agus; Hasyim Ibnu Abbas, Muhammad; Fajar Prastiwi, Lustina; Merlinda, Santi (KnE Social Sciences, 2020)
Objectives of financial management may be broadly divided into two parts such as profit maximization and wealth maximization. But alms-giving doesn’t have any connection with profit maximization or wealth maximization. Giving of alms is individual spending with non-profit oriented. Alms-giving objective for religious reason only to obey God’s order. In macro economics and micro-economics theory there are alms component as spending. Because alms-giving is better to be spent secretly. The research aims to analyze causality relationship between giving of alms with individual financial management using Econometric analysis Toda-Yamamoto causality test with E-views software. Purposive sampling method is employed to get primary data from respondents. Personal finance management is an activity that involves all the individual financial decisions, which includes budgeting, saving, insurance, mortgages. When a person plans his personal finance, he needs to take a range of financial products and other personal factors into consideration. Personal finance management has a huge influence on one’s life and future. Respondents comes from various region with various occupation and income with various religion background. Research analysis finds overwhelming support for the idea which optimism impacts economic decision-making by proving that alms affect financial management. Keywords: Alms-giving, financial management, Toda-Yamamoto causality test